PELATIHAN PENYUSUNAN DAN PENYAJIAN LAPORAN KEUANGAN UNTUK USAHA MIKRO, KECIL, DAN MENENGAH YANG BERBASIS STANDAR AKUNTANSI KEUANGAN (SAK) ENTITAS TANPA AKUNTABILITAS PUBLIK (ETAP) DI DESA MUARA JALAI KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Dini Onasis; Wita Dwika Listihana; Afvan Aquino (Universitas Lancang Kuning, 2017)
One professional management is in the preparation of financial statements follow Financial Accounting Standards (IFRSs) which has been officially in force in Indonesia as a reference book and standards in preparing and presenting financial statements of business or company. But in fact many of the micro, small and medium enterprises that do not understand the SAK. Indonesia has the Financial Accounting Standards (GAAP) used for preparing and presenting the financial statements in order to make financial statements can be uniform and easily understood by the stakeholders. Because GAAP is difficult to be applied by the economic circles of micro, small and medium then issued Financial Accounting Standards specifically for micro, small and medium enterprises by giving the name of Financial Accounting Standards ETAP (entities Without Public Accountability), so that small businesses can create financial statements in accordance with SAK ETAP. Specificity SAK ETAP is easier to be applied by SMEs but should not be applied by companies listed on the Indonesia Stock Exchange or companies that require reporting to the public. The problem that often arises is the economic society is small or micro, small and medium SAK ETAP who do not understand this, so that if they make the financial statements are not in accordance with GAAP ETAP which has been recognized by the State and International. Treatment SAK ETAP is what will be used as a workshop by TIM Faculty of Economics, University of Lancang Kuning to SMEs in the village of Muara Jalai districts of North Kampar Kampar district. TIM explains the difference SAK ETAP with the usual accounting and provide training for the preparation and presentation of financial statements in accordance with GAAP ETAP Enterprises. The SMEs estuary Jalai never prepare and present financial statements, which exist only in the traditional system even if there is only a small note on the purchase of goods. Given this devotion brings the understanding and implementation of penyususan and Presentation of financial statements based SAK ETAP which brings various benefits to SMEs.